A comparative study of dry sliding wear characterization of nano SiC and nano B4C filled Al7075 nanocomposites under high temperature environment. (1st February 2019) - Kumar, Surender; Sood, Pardeep Kumar
Abstract: The present work investigates the sliding wear behavior of aluminum matrix nanocomposites (AMNCs) fabricated through ultrasonic cavitation-assisted casting technique. The boron carbide (B4 C) and silicon carbide (SiC) nanoparticles of average size 80 nm are used as a reinforcing material and the Al7075 aluminum alloy is used as matrix material. The microstructure confirms uniform distribution of nanoparticles throughout the matrix. Hardness and tensile strength of fabricated composites increase with the addition of nano fillers. The dry sliding wear of developed nanocomposite is studied on high temperature pin disc tribometer. In order to analyze the coefficient of friction (COF) and wear rate certain parameters like normal load, parentage reinforcement of fillers, sliding velocity and pin temperature are considered as input parameters. The results obtained shows that wear rate and COF are directly proportional to pin temperature (30 °C–150 °C), normal load (5–15 N) and sliding velocity (1.5–2.5 m s −1 ) while the wear rate and COF values are inversely proportional to percentage reinforcement (0.75%–2.25%). Worn surface of nanocomposites is also analyzed through SEM analysis.